Ekokritik Cerita Bunga Rampai Sragen: Integrasi Lingkungan, Kearifan lokal dan Upaya Konservasi : Ecocriticism of Sragen Anthology Stories: Integration of Environment, Local Wisdom and Conservation Efforts. - Utama, Arip Wira; Suryanto, Edy (Information Technology and Science(ITScience), 2025)
Literature not only functions as a means of entertainment but also contains educational messages conveyed implicitly, one of which is through folklore. In the context of modern society, the issue of environmental damage is a serious problem that often escapes attention. Criticism of ecological degradation has long been implied in folklore passed down from generation to generation. This article aims to reconstruct forms of ecological criticism based on Greg Garrard's ecocritical theory and explore environmental conservation efforts through local wisdom values in the Toponymy Bunga Rampai Village Story in Sragen Regency. This study uses a descriptive qualitative method with listening and note-taking techniques to select stories containing ecological criticism elements. The results of the survey showed 18 findings of ecological criticism from 10 folklore, consisting of five criticisms of the wilderness, five of animals, four of the earth, three of the living environment, and one of pollution. These findings indicate that folklore is not only a reflection of culture but also a means of educational criticism of environmental issues. By linking these criticisms to local wisdom values, this article concludes that folklore contributes to conservative efforts in a preventive manner against the ecological crisis through a more down-to-earth and contextual approach to the power of local wisdom values.